Pemanfaatan Kecerdasan Artifisial untuk Menciptakan Perangkat Pembelajaran yang Menarik dan Efektif di Taman Kanak-Kanak - Ghema Nusa Persada; Salman Farizy; Endin Fahrudin (Jurnal Sinergi Sistem Informasi Pengabdian Masyarakat, 2025)
Education in early childhood is a crucial foundation for character building and creativity. However, the learning process at TK Baitul Karim remains conventional, dominated by lecture methods and manual worksheets, leading to low student engagement. The identified problems include teachers' low digital competence and a lack of interactive media. This community service aims to implement Artificial Intelligence (AI) technology to help teachers develop digital, adaptive, and fun learning tools. The methods used include situational analysis, training on AI platforms (ChatGPT, DALL·E, Canva AI), intensive mentoring, and pilot implementation in class. The results show a significant increase in teachers' digital literacy, with a 60% improvement in post-test scores. Furthermore, 100% of participants successfully created AI-based media such as automated picture books and educational videos. Implementation in the classroom resulted in increased student focus and interaction. This program demonstrates that AI can be a practical solution for creating innovative learning media in early childhood education.